Mechanisms of repigmentation induced by photobiomodulation therapy in vitiligo. (30th January 2019) - Yu, Sebastian; Lan, Cheng‐Che E.; Yu, Hsin‐Su
Abstract: Photobiomodulation (PBM) therapy is based on the exposure of biological tissues to low‐level laser light (coherent light) or light‐emitting diodes (LEDs; noncoherent light), leading to the modulation of cellular functions, such as proliferation and migration, which result in tissue regeneration. PBM therapy has important clinical applications in regenerative medicine. Vitiligo is an acquired depigmentary disorder resulting from disappearance of functional melanocytes in the involved skin. Vitiligo repigmentation depends on available melanocytes derived from (a) melanocyte stem cells located in the bulge area of hair follicles and (b) the epidermis at the lesional borders, which contains a pool of functional melanocytes. Since follicular melanoblasts (MBs) are derived from the melanocyte stem cells residing at the bulge area of hair follicle, the process of vitiligo repigmentation presents a research model for studying the regenerative effect of PBM therapy. Previous reports have shown favourable response for treatment of vitiligo with a low‐energy helium‐neon (He‐Ne) laser. This review focuses on the molecular events that took place during the repigmentation process of vitiligo triggered by He‐Ne laser (632.8 nm, red light). Monochromatic radiation in the visible and infrared A (IRA) range sustains matrix metalloproteinase (MMP), improves mitochondrial function, and increases adenosine triphosphate (ATP) synthesis and O2 consumption, which lead to cellular regenerative pathways. Cytochrome c oxidase in the mitochondria was reported to be the photoacceptor upon which He‐Ne laser exerts its effects. Mitochondrial retrograde signalling is responsible for the cellular events by red light. This review shows that He‐Ne laser initiated mitochondrial retrograde signalling via a Ca 2+ ‐dependent cascade. The impact on cytochrome c oxidase within the mitochondria, an event that results in activation of CREB (cyclic‐AMP response element binding protein)‐related cascade, is responsible for the He‐Ne laser promoting functional development at different stages of MBs and boosting functional melanocytes. He‐Ne laser irradiation induced (a) melanocyte stem cell differentiation; (b) immature outer root sheath MB migration; (c) differentiated outer root sheath MB melanogenesis and migration; and (d) perilesional melanocyte migration and proliferation. These photobiomodulation effects result in perifollocular and marginal repigmentation in vitiligo.